EFFECT OF EYESTALK EXTIRPATION ON LARVAL DEVELOPMENT OF THE SHRIMP, MACROBRACHIUM LAMERRII - SUGUNA, P.; SAROJINI, R.; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The effect of eyestalk extirpation on larval development of freshwater prawn, M. lamerri was observed. Removal of only one eyestalk at any period during development did not alter the sequence of larval stages or molting frequency. Extirpation of both eyestalks prior to day 2, stage IV resulted in supernumerary larval stages and only the post moltintervals of postlarval stages were shortened. The production of supernumerary larval stages and absence of acceleration in molting during larval stages in ablated larvae is discussed.